2022
DOI: 10.4187/respcare.09937
|View full text |Cite
|
Sign up to set email alerts
|

Intubation Timing in COVID-19 Based on ROX Index and Association With Patient Outcomes

Abstract: BACKGROUND: Timing of intubation in COVID-19 is controversial. We sought to determine the association of the ROX (Respiratory rate-OXygenation) index defined as S pO 2 divided by F IO 2 divided by breathing frequency at the time of intubation with clinical outcomes. METHODS: We conducted a retrospective cohort study of patients with COVID-19 who were intubated by using a database composed of electronic health record data from patients with COVID-19 from 62 institutions. Multivariable logistic regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
3
0
1
Order By: Relevance
“…Specifically, our findings suggest that combination therapy with different classes of drugs is more effective than therapy with only a single agent. These models also demonstrate that patient characteristics and comorbidities such as age, kidney, liver, heart disease, and severity of illness at diagnosis have a large impact on disease outcome, confirming previous literature [25][26][27][28][29]. Indeed, the models suggest that for COVID-19 outcomes, patient characteristics are not surprisingly often as influential as the treatments administered.…”
Section: Plos Onesupporting
confidence: 84%
“…Specifically, our findings suggest that combination therapy with different classes of drugs is more effective than therapy with only a single agent. These models also demonstrate that patient characteristics and comorbidities such as age, kidney, liver, heart disease, and severity of illness at diagnosis have a large impact on disease outcome, confirming previous literature [25][26][27][28][29]. Indeed, the models suggest that for COVID-19 outcomes, patient characteristics are not surprisingly often as influential as the treatments administered.…”
Section: Plos Onesupporting
confidence: 84%
“…These results were confirmed in a sub-analysis of FLORALI [7]. The ROX score was also retrospectively studied in a cohort of patients with COVID-19, which confirmed that increasing ROX index score at the time of intubation was associated with greater survival [55].…”
Section: Ventilatory Management Of Respiratory Failure Caused By Sars...supporting
confidence: 60%
“…The target saturation range of 92%-96% used in practice was derived from data in ARDS patients, in whom both low saturations (<92%) [61] and high saturations (>96%) [204] are detrimental. Reduced peripheral oxygen saturation acts as both a risk factor for intubation [205][206][207] and a guide to the timing of assisted ventilation [208,209]. Moreover, after COVID-19 patients have been intubated, further declines in oxygenation continue to be predictive of mortality risk [210], and improvements in saturation readings can act as a guide to the effectiveness of prone ventilation therapy [211].…”
Section: Peripheral Oxygen Saturationmentioning
confidence: 99%